Analysis of Recuperated Combined Cycle with Small Temperature Rise under Design/Off-design Conditions. (May 2017) - Zhang, Guoqiang; Bai, Ziwei; Yang, Yongping
Abstract: This paper aims to analyze the performance characteristics of recuperated combined cycle, in which the recuperator is arranged inside HRSG, under design/off-design conditions. The recuperator is located between the first high pressure superheater and evaporator. The recuperated combined cycle is modeled and its performance is simulated with different operation strategies. The results show that the combined cycle efficiency can be improved by using this recuperator under both full and part load conditions. The temperature rise of recuperated air in the recuperator has great impact on the performance of this recuperated unit. Operation strategy of kept turbine inlet temperature (T3) as high as possible via variable inlet guide vane (IGV) control shows advantage in combined cycle efficiency and recuperated characteristic. The combined cycle efficiency can be increased by maximum of 1.2% under part load by recuperator retrofitting based on the common combined cycle. In addition, the specific work under varied significantly, which shows a better option for part load control by using recuperation.